Management of Education: Historical Discourse - Darmanskaya, Iryna (Pedagogical Discourse, 2012)
The article describes the historical periods of educational sphere development, which were characterized by the existence of certain institutions playing role of education organizers and conducting management of this process in the state as a whole, and in some of it political units.